(untitled) (International Journal of Physiotherapy, 2026)
Background: High-risk infants are vulnerable to adverse neurodevelopmental outcomes despite improved neonatal survival. Early, parent-mediated interventions that enhance caregiver–infant interaction are crucial during the first months of life. Reach Out and Read (ROR) is a literacy-based program that has been shown to promote early development. Yet, evidence of its effect on global neurodevelopment in high-risk infants in early infancy remains limited. Methods: A randomized controlled trial with a parallel-group design was conducted at a tertiary care hospital in Belagavi. Thirty-two high-risk infants (2 weeks of age) were randomly allocated to an experimental (ROR) or control (standard care) group. Infants in the experimental group received a vernacular ROR book with structured, age-appropriate activities and parental guidance, reinforced through follow-up calls and clinic visits. Neurodevelopment was assessed at 6, 10, and 14 weeks of age using the Caregiver Reported Early Development Instrument (CREDI). Results: Data were analysed using descriptive statistics and repeated-measures ANOVA, with significance set at p < 0.05. Baseline infant and parental characteristics were comparable between groups. Significant improvements over time were observed across all developmental domains in both groups (p < 0.001). However, significant time × group interactions favored the ROR group for language (F = 54.23, p < 0.001), motor (F = 18.86, p < 0.001), and socio-emotional domains (F = 4.04, p = 0.029). Effect size analysis demonstrated the largest intervention effects for language (partial η² = 0.383) and overall development (partial η² = 0.37). Conclusion: The ROR program is an effective early intervention to enhance language, motor, and socio-emotional development in high-risk infants during the early months of life. Integrating culturally adapted, parent-mediated literacy interventions may strengthen developmental outcomes and caregiver engagement alongside standard care.